Corporate Social Responsibility and SME Value Creation - Asit Bhattacharyya; Amit Kumar (Australasian Accounting, Business and Finance Journal, 2022)
Despite small and medium-sized enterprises (SMEs) ability to contribute in achieving sustainable economic growth, to reduce unemployment, value creation ability of SMEs through CSR remains unexplored. We examine the impact of CSR on SME value in manufacturing and service industries context, the industries ignored by existing research. We also explore the interactive relationship of CSR and access to finance and their impact on CSR-Value relationship. Our key finding is that SMEs value is positively associated with the CSR expenditure and access to finance. The results indicate that current year CSR expenditure creates value for SMEs through improving their access to finance and ultimately improving their sales in the next year but do not moderate the CSR-Value relationship . Our results are robust and reliable because we employed both 2SLS and generalised method of moments (GMM) approaches to address possible endogeneity. Moreover, we use actual CSR spending data from developing country instead of CSR scores as a proxy for CSR expenditures usually used by prior studies concentrating only on large firms. Our results could be used by the policy makers and regulators in other emerging countries to justify the introduction of schemes to improve CSR and access to finance for SMEs.
Keywords: SME; CSR spending; SME value; access to finance